Suicide risk and media consumption in the COVID-19 pandemic in Colombia (2023)
The media can play an important role in suicide prevention and mental health care, especially in a country like Colombia, affected by an internal armed conflict, and with worrying cases of suicide that increased during the COVID-19 pandemic. It is known that mental health conditions were accentuated during the first year of this pandemic, with the deaths of family and friends, mandatory isolation, and the economic crisis, among others. This study examines the relationship between media reception and suicidal ideation in Colombia during this period. Methodologically, this predictive, cross-sectional, and non-experimental correlational study presents the results of a survey of Colombians aged 18 to 59 (N=660) from the three most populated regions of the country, conducted from January 1 to November 30, 2020. It was found that both frequent reception of news about deaths coronavirus, as well as the intentional search for or access to information in the media about suicide cases, acted as risk predictors of suicidal ideation. Conversely, the reception of programs that promoted or strengthened spiritual life was a protective factor against suicidal ideation. Age and physical and mental health did not influence the relationship between suicidal ideation and the reception of information about these human losses. In conclusion, the way in which a pandemic and suicide cases are journalistically covered influences suicidal ideation. Exposure to audiovisual entertainment programs could help lower the levels of suicidal ideation in contexts of a health crisis, as long as they emphasize the support networks and the reasons for living that are present in the programs that promote spiritual life.